Dephosphorisation of steel slags by leaching with sulphuric acid. Issue 4 (2nd October 2018) - Qiao, Yong; Diao, Jiang; Liu, Deman; Yang, Jianfeng; Guo, Dongwei; Gong, Siyu; Xie, Bing
ABSTRACT: Dephosphorisation is of great significance for the recycling of steel slags in iron and steel industry. In this paper, the dephosphorisation of steel slags by leaching with sulphuric acid was investigated. The influential factors such as leaching time, sulphuric acid concentration, temperature, particle size and liquid/solid ratio were optimised. Over 92% of the phosphorus can be dissolved in the sulphuric acid solution while the corresponding iron loss was 34% under the condition of 60 min, sulphuric acid concentration 2.5%, 30°C, particle size <75 μm and liquid/solid ratio 100. The kinetics of the dephosphorisation process of steel slags by leaching with sulphuric acid was analysed and it was demonstrated that the unreacted shrinking core model was suited for the present study. The diffusion through solid layer around the unreacted core was the rate-limiting step of the leaching process.